Back to “I Do”: strengthening marriages in Singapore - Ningrong, Chiam (2016)
Back to “I Do” is an integrated public relations campaign led by four final year undergraduates from Nanyang Technological University, Wee Kim Wee School of Communication and Information. Targeted at married couples in the Strawberry Stage, aged 30 to 39, the campaign aims to strengthen marital bonds among couples in Singapore by motivating them to not only have a functional marriage, but also a fulfilling one through increasing their marital satisfaction in three ways: (1) increasing their commitment level, (2) increasing their intimacy level, and (3) improving their conflict resolution skills. Based on the AIDAR model, Back to “I Do” employs the use of both traditional and new media techniques to garner attention and interest in three phases. The team held multiple roadshows in various parts of Singapore which culminates in a Couples’ Retreat. The campaign secured a total of $56,784 in terms of sponsorship value. In return, the campaign’s advertising value equivalent (AVE) is worth $16,154 with a total offline and online impression count of 14,787,523. This report presents a summary of the primary and secondary research which guide the campaign’s communication tactics, creative execution, and an evaluation of the campaign’s effectiveness. The latter includes post-campaign surveys, testimonials, metrics from both online and offline publicity efforts, and an analysis of traditional and new media coverage. The report concludes with an assessment of limitations and recommendations for the campaign. The appendix comprises of materials that complement the main text, providing a detailed background to the campaign process.